Development of E-Assessment Instruments for Assessing Metacognition Skills of Students in The Research Methodology Course - Nurnaningsih , Nurnaningsih; Amrin, Amrin (Yupa: Historical Studies Journal, 2024)
This research is focused on the creation of a valid and dependable tool designed for the assessment of students' metacognitive abilities within the context of the Research Methodology course. The research methodology employed for this research follows the Research and Development (R&D) framework outlined by Mardapi, which encompasses ten distinct phases. The participants involved in this research comprised four lecturers responsible for instructing research methodology courses and a total of 61 students who were enrolled in these courses. The data collected for this research consisted of quantitative data acquired through expert validation questionnaires and trial instruments. Data analysis was conducted employing quantitative techniques, specifically utilizing Microsoft Excel and employing the Item Response Theory (IRT) Politomus data analysis approach within the R programming environment. The research outcomes indicated that the instrument employed to evaluate students' metacognitive skills in the research methodology course achieved a valid status as per expert evaluations, meeting the criteria for goodness. It was found to be valid in terms of the response distribution across all 24 items, and collectively, the instrument items were deemed capable of offering insights into the state of the test participants (respondents) by more than 85%. Moreover, the instrument demonstrated a very high level of reliability as 0,94.